(untitled) (Configurazioni. Research on contemporary poetry, 2023)
20th Century Italian poetry anthologies in translation are fundamental vehicles of its reception abroad. Four Anglo-American and three French works from the 1960s onwards are analyzed according to an approach whose most innovative aspects are the comparative study of reception in different linguistic-cultural contexts, and the investigation of the role of poets in the genesis of the anthologies through the philological examination of their correspondence with the editors.